'Ages five and up': Alien toys for children and the question of horror's histories. Issue 1 (1st April 2022) - Antunes, Filipa; Plowman, Alec
This article considers the children's toys made by Kenner for the original release of Alien (1979) and argues that they present a challenge to some of the most frequently repeated assumptions about the horror genre and its history. Specifically, the article questions the 'natural' association between horror and transgression, and the genre's supposed separation from child audiences, noting the way these assumptions become tangled with notions of quality. The article historicizes Kenner's Alien line in the context of the 1970s toy industry and the rest of children's culture, including film franchises, where horror and monster adventures were popular children's entertainment. The article then matches these findings to an analysis of Alien's original critical reception, suggesting Alien as a text held between coexisting definitions of horror in 1970s culture: a genre for all-ages entertainment, as defined dominantly across pop culture, but also a (film) genre where emerging intensity was allowed by the newly introduced R rating. The article thus argues for the need to question traditional histories of horror and re-examine their limiting assumptions about children, transgression and quality. Moreover, the article highlights the need to look beyond single media industries when exploring the cultural expression of the horror genre and of 'canonical' texts, especially where franchise relationships are involved.